ROS regulation of polar growth in plant cells - Mangano, Silvina (2016)
Root hair cells and pollen tubes, like fungal hyphae, possess a typical tip or polar cell expansion with growth limited to the apical dome. Cell expansion needs to be carefully regulated to produce a correct shape and size. Polar cell growth is sustained by oscillatory feedback loops comprising three main components that together play an important role regulating this process. One of the main components are reactive oxygen species (ROS) that, together with calcium ions (Ca(2+)) and pH, sustain polar growth over time. Apoplastic ROS homeostasis controlled by NADPH oxidases as well as by secreted type III peroxidases has a great impact on cell wall properties during cell expansion. Polar growth needs to balance a focused secretion of new materials in an extending but still rigid cell wall in order to contain turgor pressure. In this review, we discuss the gaps in our understanding of how ROS impact on the oscillatory Ca(2+) and pH signatures that, coordinately, allow root hair cells and pollen tubes to expand in a controlled manner to several hundred times their original size toward specific signals